Development of a prototype thermodynamic database for Nd-Fe-B permanent magnets. Issue 1 (31st December 2021) - Abe, Taichi; Morishita, Masao; Chen, Ying; Saengdeejing, Arkapol; Hashimoto, Kiyoshi; Kobayashi, Yoshinao; Ohnuma, Ikuo; Koyama, Toshiyuki; Hirosawa, Satoshi
ABSTRACT: For the Nd-Fe-B permanent magnets, a prototype thermodynamic database of the 8-element system (Nd, Fe, B, Al, Co, Cu, Dy, Ga) was constructed based on literature data and assessed parameters in the present work. The magnetic excess Gibbs energy of the Nd2 Fe14 B compound was reassessed using thoroughly measured heat capacity data. The Dy-Nd binary system was reassessed based on formation energies estimated from ab initio calculations. The constructed database was applied successfully for estimations of phase equilibria during the grain boundary diffusion processes (GBDP) and the reactions in the hydrogenation decomposition desorption recombination (HDDR) processes. Graphical abstract: uf0001